A search for excited fermions in e+p collisions at HERA - Breitweg, J; Derrick, M; Krakauer, D; Magill, S; Mikunas, D; Musgrave, B; Repond, J; Stanek, R; Talaga, R; Yoshida, R; Zhang, H; Mattingly, M; et al. (1997)
Using the ZEUS detector at HERA, we have searched for heavy excited states of electrons, neutrinos, and quarks in e+p collisions at a center-of-mass energy of 300 GeV. With an integrated luminosity of 9.4 pb-1, no evidence was found for electroweak production and decay of such states. Limits on the production cross section times branching ratio and on the characteristic couplings, f/Λ, are derived for masses up to 250 GeV. For the particular choice f/Λ = 1/Mf*, we exclude at the 95% confidence level excited electrons with mass between 30 and 200 GeV, excited electron neutrinos with mass between 40 and 96 GeV, and quarks excited electroweakly with mass between 40 and 169 GeV. © Springer-Verlag 1997.